2009
DOI: 10.7205/milmed-d-03-4307
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Deployment Intensity on Post-Traumatic Stress Disorder: 2002–2006

Abstract: Our results highlight the importance of providing adequate mental health care resources for those returning from hostile deployments and raise concerns about combat effectiveness of long deployments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 13 publications
2
35
1
Order By: Relevance
“…However, the lack of reliable associations between longer duration of deployment and subsequent poor health contradicts most literature in the area [2,35,149,159,172]. Current findings may be attributed to 'the healthy soldier effect' (that is, those who are deployed multiple times may be healthier than their never or less frequently deployed counterparts) or 'combat seasoning' (combat-related experiences on deployment may increase the physical and psychological resilience of veterans compared to their less experienced counterparts) [6,149].…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…However, the lack of reliable associations between longer duration of deployment and subsequent poor health contradicts most literature in the area [2,35,149,159,172]. Current findings may be attributed to 'the healthy soldier effect' (that is, those who are deployed multiple times may be healthier than their never or less frequently deployed counterparts) or 'combat seasoning' (combat-related experiences on deployment may increase the physical and psychological resilience of veterans compared to their less experienced counterparts) [6,149].…”
Section: Discussionmentioning
confidence: 69%
“…Studies from several countries focusing on a variety of operational deployments have suggested that prolonged duration and high frequency of military deployments to hostile environments can have detrimental effects on the mental and physical health of military personnel [2,25,35,68,146,149,159,172]. Associations have been demonstrated between deployment length and alcohol misuse [149,172], symptoms of posttraumatic stress [2,149,159], poor general health [149], depression [2], and self-reports of multiple physical symptoms [149].…”
Section: Patterns Of Deploymentmentioning
confidence: 99%
See 2 more Smart Citations
“…Among recently returning veterans, an increase in the prevalence of PTSD has been associated with multiple factors, including (1) exposure to combat [47], (2) battle versus nonbattle injuries [50], (3) increase of deployment intensity and duration [51], and (4) blast injuries as opposed to other mechanisms of injury [9]. Elements of modern body armor, improved battlefield healthcare, and rapid medical evacuation have helped decrease combat-related mortality with an associated increase in the percentage of soldiers surviving severe traumatic injuries [49,[52][53].…”
Section: Discussionmentioning
confidence: 99%